The last samurai - Zwick, Edward; Logan, John; Herskowitz, Marshall; Warner Bros. Pictures (Burbank, CA : Warner Home Video, 2004)
Civil war hero Nathan Algren is sent to Japan during the Meiji era in order to train troops to use firearms against the samurai. Soon Algren finds himself swept up in the samurai way of life after being captured by their leader
Title from title screen
Subtitles in English, Chinese, English Narrative and Malay
Executive producer, Ted Field...[et al.] ; screenplay by John Logan, Edward Zwick, and Marshall Herskovitz
Cast: Ken Watanabe, Tom Cruise, William Atherton